PERAN DINAS KESEHATAN DALAM PENANGGULANGAN HUMAN IMMUNODEFICIENCY VIRUS -ACQUIRED IMMUNO DEFICIENCY SYNDROME (HIV-AIDS) SESUAI PERATURAN DAERAH NOMOR 2 TAHUN 2013 (Studi Di Kabupaten Kebumen) - Rachmadi, Triyo (Jurnal Idea Hukum, 2015)
Efforts to control HIV-AIDS is a program of technical effort in order to control the spread of HIV-AIDS in the health sector. The role of the District Health Office Kebumen responsible for organizing health service very necessary. This study aims to determine the role of law in the regulation of the subject area is to comply with its obligations and driving as well as the constraints faced in the prevention of HIV-AIDS in Kebumen. This study uses a socio-juridical approach to the primary data source and secondary data. Collecting data with the study of documents, observations and interviews with informants. Location of research in the District, Health, Office, Kebumen. The results showed that of the six indicators of HIV-AIDS organizing appropriate Local Regulations Number 2 of years 2013 has not been implemented. These six indicators are policies and strategies, prevention of HIV-AIDS, HIV-AIDS treatment, rehabilitation of HIV-AIDS, Local Government responsibilities and obligations, prohibitions, administrative sanctions. Thus the role of the District Health Office Kebumen in HIV-AIDS accordance Local Regulation Number 2 of Years 2013 is still lacking. Keywords: District Health Office, HIV-AIDS, Local Regulations